Hypertrophic Cardiomyopathy in Patients with Atrial Fibrillation: Prevalence and Associated Stroke Risks in a Nationwide Cohort Study - Jung, Hyunjean; Yang, Pil-Sung; Sung, Jung-Hoon; Jang, Eunsun; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Kim, Jong-Youn; Pak, Hui-Nam; Lee, Moon-Hyoung; Lip, Gregory Y. H.; Joung, Boyoung (Thrombosis and Haemostasis, 2019)
Background There have been no prior nationwide reports on the prevalence of hypertrophic cardiomyopathy (HCM) among patients suffering from atrial fibrillation (AF). It is also unclear how much stroke risk is attributable to HCM compared with other stroke risks in patients with AF. This study assessed the prevalence of HCM among non-valvular AF (NVAF) patients and to assess the magnitude of increase in stroke risk in NVAF patients with HCM, compared with those without HCM.Patients and Methods From the Korean National Health Insurance Service database from January 1, 2005 to December 31, 2016, we analysed 979,784 patients with prevalent NVAF aged 18 years or older.Results The overall HCM prevalence in NVAF patients was 1.1%. Although HCM in these patients is an absolute indication for oral anticoagulant (OAC) prescription, only 1,622 (15.3%) patients were receiving OAC at the time of AF diagnosis. Among OAC-naïve patients with NVAF, compared with those without HCM, those with HCM had the increased risk of ischaemic stroke/systemic embolism with clinical variable adjusted hazard ratio of 1.55 (95% confidential interval, 1.48–1.63; p < 0.001). Ischaemic stroke/systemic embolism rate of NVAF patients with HCM without any non-gender CHA2DS2-VASc stroke risk factors was 4.02 per 100 person-years, and approached to that of NVAF patients without HCM with CHA2DS2-VASc score of 3 (4.07 per 100 person-years).Conclusion Among all NVAF patients, 1.1% of patient has HCM. The risk of stroke in NVAF with HCM without any CHA2DS2-VASc stroke risk factors was similar to that of those patients without HCM with CHA2DS2-VASc score of 3. Despite this, the actual use of OACs among NVAF patients with HCM was sub-optimal, relative to their high stroke risk.
Keywords: atrial fibrillation; hypertrophic cardiomyopathy; stroke